En el trasfondo de la ‘colombianización’: el archipiélago de San Andrés visto por funcionarios del Estado colombiano (1888-1924) - Charry Joya, Carlos Andrés (Sociedad y Economía, 2002)
This paper approaches the continental images that framed the conflictive relations between the Colombian State and the population of the San Andres islands, as an attempt to assess the socio-cultural impact of the process of the State formation upon this region. The research produces a recount of the process of formation of “Colombianness” among the local people, a continental policy destined to integrate the native population of San Andres to the national social dynamics. The details of this policy are interpreted from the observations made by three continental visitors who were in the Islands during that period; they attest to the deviation and difficult assimilation that affected the making of “Colombianness” at the local level.